Evaluation of respiratory dynamics by volumetric capnography during submaximal exercise protocol of six minutes on treadmill in cystic fibrosis patients - Paloma L.F. Parazzi; Fernando A.L. Marson; Maria A.G.O. Ribeiro; Camila I.S. Schivinski; José D. Ribeiro (Brazilian Society of Pediatrics, 2019)
Objectives: Volumetric capnography provides the standard CO2 elimination by the volume expired per respiratory cycle and is a measure to assess pulmonary involvement. Thus, the objective of this study was to evaluate the respiratory dynamics of healthy control subjects and those with cystic fibrosis in a submaximal exercise protocol for six minutes on the treadmill, using volumetric capnography parameters (slope 3 [Slp3], Slp3/tidal volume [Slp3/TV], and slope 2 [Slp2]). Methods: This was a cross‐sectional study with 128 subjects (cystic fibrosis, 64 subjects; controls, 64 subjects]. Participants underwent volumetric capnography before, during, and after six minutes on the treadmill. Statistical analysis was performed using the Friedman, Mann-Whitney, and Kruskal-Wallis tests, considering age and sex. An alpha = 0.05 was considered. Results: Six minutes on the treadmill evaluation: in cystic fibrosis, volumetric capnography parameters were different before, during, and after six minutes on the treadmill; the same was observed for the controls, except for Slp2. Regarding age, an Slp3 difference was observed in cystic fibrosis patients regardless of age, at all moments, and in controls for age ≥ 12 years; a difference in Slp3/TV was observed in cystic fibrosis and controls, regardless of age; and an Slp2 difference in the cystic fibrosis, regardless of age. Regarding sex, Slp3 and Slp3/TV differences were observed in cystic fibrosis regardless of sex, and in controls in male participants; an Slp2 difference was observed in the cystic fibrosis and female participants. The analysis between groups (cystic fibrosis and controls) indicated that Slp3 and Slp3/TV has identified the CF, regardless of age and sex, while the Slp2 showed the CF considering age. Conclusions: Cystic fibrosis showed greater values of the parameters before, during, and after exercise, even when stratified by age and sex, which may indicate ventilation inhomogeneity in the peripheral pathways in the cystic fibrosis. Resumo: Objetivos: A capnografia volumétrica fornece o padrão de eliminação do CO2, pelo volume expirado por ciclo respiratório e avalia o comprometimento pulmonar. O objetivo do estudo foi avaliar a dinâmica respiratória de indivíduos controles saudáveis e em indivíduos com fibrose cística, em um protocolo de exercício submáximo por seis minutos em esteira, por parâmetros da capnografia volumétrica [slope 3(Slp3), Slp3/volume corrente (Slp3/TV) e slope 2(Slp2)]. Métodos: Estudo de corte transversal com 128 indivíduos [(fibrose cística) 64 indivíduos; (controles) 64 indivíduos]. Os participantes realizaram capnografia volumétrica antes, durante e após seis minutos em esteira. Análise estatística realizada pelos testes de Friedman, Mann-Whitney e Kruskal-Wallis, considerado a idade e o sexo. Alpha = 0,05. Resultados: Avaliação de seis minutos em esteira: na fibrose cística, os parâmetros da capnografia volumétrica foram diferentes antes, durante e após seis minutos em esteira, o mesmo ocorreu nos controles, exceto para o Slp2. Considerando a idade: (Slp3) diferença na FC, independentemente da idade, em todos os momentos e nos controles apenas para ≥ 12 anos; (Slp3/TV) diferença para fibrose cística e controles independentemente da idade; (Slp2) diferença apenas para o grupo fibrose cística, independentemente da idade. Considerando o sexo: (Slp3 e Slp3/TV) diferença para fibrose cística, independentemente do sexo, e controles apenas no sexo masculino; (Slp2) diferença para fibrose cística e sexo feminino. Análise entre grupos (fibrose cística versus controles): Slp3 e Slp3/TV identificou a fibrose cística, independentemente da idade e sexo, enquanto o Slp2 evidenciou a fibrose cística considerando a idade. Conclusão: A fibrose cística apresentou maiores valores dos parâmetros antes, durante e após exercício, inclusive quando se considerou idade e sexo, podendo indicar não homogeneidade da distribuição da ventilação nas vias periféricas. Keywords: Breath, CFTR, Exercise, Pulmonary function, Slope 2, Slope 3, Palavras‐chave: Respiração, CFTR, Exercício, Função pulmonar, Slope 2, Slope 3